Thymidine phosphorylase expression in normal and hyperplastic endometrium - Sivridis, E. (2000)
Aims—To investigate the expression of thymidine phosphorylase (TP), a known angiogenic factor for endothelial cells, in normally cycling endometrium and various forms of endometrial hyperplasia. Methods—TP expression was assessed with the P-GF.44C monoclonal antibody, using the alkaline phosphatase anti-alkaline phosphatase method. Ninety two normal and hyperplastic endometria were studied. Results—In normal proliferative endometrium, TP is found exclusively in the basal layer and the inner third of the functionalis; expression is cytoplasmic in glandular epithelium and nuclear in stromal cells. It is invariably patchy. This immunohistochemical picture remains almost unaltered during the early and mid secretory phase of the normal menstrual cycle but, most impressively, TP is expressed uniformly in the epithelium of all endometrial glands towards the end of the cycle. At this stage, expression is mixed nuclear/cytoplasmic and there is very little stromal nuclear staining. In simple endometrial hyperplasia, the staining pattern for TP is identical to normal proliferative endometrium, with a distribution that is usually limited to a few rather weakly proliferating glands and to the adjacent periglandular stroma of the deep endometrium. The distribution is more extensive in complex and atypical endometrial hyperplasias, where a mixed nuclear/cytoplasmic pattern usually prevails over the pure cytoplasmic reaction. Conclusions—TP is expressed consistently in normal and hyperplastic endometrium, suggesting a role in physiological and pathological angiogenesis. In normal endometrium, TP has a definite pattern of distribution, which is dependent on the phase of the menstrual cycle, whereas in all forms of endometrial hyperplasia the enzyme is randomly distributed and lacks an orderly pattern. Key Words: thymidine phosphorylase • normal endometrium • hyperplastic endometrium